Synthesis of 2-phenyl-5, 6, 7, 8-tetrahydroquinoxaline derivatives and screening for P2X1-purinoceptor antagonist activity in isolated preparations of rat vas deferens, for translation into a male contraceptive. Issue 2 (10th July 2020) - Mathiew, Mitch; Dennis, Belinda M; Bennetts, Felix; Su, N N Eunice; Nguyen, Nghi; Botteon, Antony; Baell, Jonathan B; Ventura, Sabatino
Abstract: Sympathetically mediated contractions of smooth muscle cells in the vasa deferentia are mediated by neuronally released adenosine 5′-triphosphate (ATP) and noradrenaline, which stimulate P2X1-purinoceptors and α1A -adrenoceptors, respectively. This process is crucial for sperm transport, as demonstrated in knockout mouse studies where simultaneous genetic deletion of P2X1-purinoceptors and α1A -adrenoceptors resulted in male infertility. We hypothesize that dual pharmacological antagonism of these two receptors could inhibit sperm transport sufficiently to provide a novel nonhormonal method of male contraception. To generate a suitable P2X1-purinoceptor antagonist, substituents were introduced on the phenyl moiety of 2-phenyl-5, 6, 7, 8-tetrahydroquinoxaline to create a series of analogues that were tested for P2X1-purinoceptor antagonism in isolated preparations of rat vas deferens. Novel compounds were initially screened for their ability to attenuate contractile responses to electrical field stimulation (EFS: 60 V, 0.5 ms, 0.2 Hz). The addition of polar substituents to the meta, but not ortho, position markedly increased the inhibition of contractions, as did the addition of both polar and aliphatic substituents to the para position. Di-substituted compounds were also synthesized and tested, resulting in a compound 31 (2-hydroxy, 4-fluoro), which exhibited the greatest potency, with an IC50 of 14 μM (95% confidence limits: 12–16 μM). Additionally, compound 31 noncompetitively antagonized contractions mediated by exogenously administered αß-methylene ATP (10 nM–30 μM) but had no inhibitory effect on contractions mediated by exogenously administered noradrenaline (30 nM–100 μM) or acetylcholine (30 nM–100 μM). These results have contributed to a structure–activity relationship profile for the P2X1-purinoceptor that will inform future designs of more potent antagonists. Abstract : Novel small molecule P2X1-purinoceptor antagonists were able to selectively inhibit the purinergic component of contractions of the rat vas deferens. Graphical Abstract: